2011
DOI: 10.1177/1359105310384296
|View full text |Cite
|
Sign up to set email alerts
|

Putting the positive in health psychology: A content analysis of three journals

Abstract: This content analysis investigated the inclusion of positive psychological constructs in research published in three leading health psychology journals. A list of positive constructs relevant to health psychology was compiled and their inclusion in these journals was examined. It was found that although there has been a sharp increase in recent years, only 3 percent of all articles published (114 of 3789) included the study of overtly positive constructs. The constructs that have been most and least studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 49 publications
2
30
0
2
Order By: Relevance
“…Social, environmental, and economic factors have all been demonstrated to impact on physical and mental health by affecting behaviour, lifestyle, and the ability to implement positive change (Marks, 2002;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011;Upton & Thirlaway, 2014;Webb, 2012). Social, environmental, and economic factors have all been demonstrated to impact on physical and mental health by affecting behaviour, lifestyle, and the ability to implement positive change (Marks, 2002;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011;Upton & Thirlaway, 2014;Webb, 2012).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Social, environmental, and economic factors have all been demonstrated to impact on physical and mental health by affecting behaviour, lifestyle, and the ability to implement positive change (Marks, 2002;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011;Upton & Thirlaway, 2014;Webb, 2012). Social, environmental, and economic factors have all been demonstrated to impact on physical and mental health by affecting behaviour, lifestyle, and the ability to implement positive change (Marks, 2002;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011;Upton & Thirlaway, 2014;Webb, 2012).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…As such, psychological health could prove one explanation for any link between gratitude and physical health. However, work is still needed to examine whether psychological health serves to describe linkages between positive psychology constructs, like gratitude, and physical health (Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Research on positive psychology has identified protective resources (e.g., optimism, control, meanings of life) that improve mental health status of PLWH (Taylor, Kemeny, Reed, Bower, & Gruenewald, 2000). Resilience is one of the key themes of positive psychology (Hart & Sasso, 2011;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011). Resilience is one of the key themes of positive psychology (Hart & Sasso, 2011;Schmidt, Raque-Bogdan, Piontkowski, & Schaefer, 2011).…”
mentioning
confidence: 99%